Identification of Breast Cancer Stem Cell Related Genes Using Functional Cellular Assays Combined With Single-Cell RNA Sequencing in MDA-MB-231 Cells - Jonasson, Emma; Ghannoum, Salim; Persson, Emma; Karlsson, Joakim; Kroneis, Thomas; Larsson, Erik; Landberg, Göran; Ståhlberg, Anders (Frontiers in Genetics, 2019)
Breast cancer tumors display different cellular phenotypes. A growing body of evidence points towards a population of cancer stem cells that is important for metastasis and treatment resistance, although the characteristics of these cells are incomplete. We used mammosphere formation assay and label-retention assay as functional cellular approaches to enrich for cells with different degree of cancer stem cell properties in the breast cancer cell line MDA-MB-231 and performed single-cell RNA sequencing. We clustered the cells based on their gene expression profiles and identified three subpopulations, including a cancer stem cell-like population. The cell clustering into these subpopulations overlapped with the cellular enrichment approach applied. To molecularly define these groups, we identified genes differentially expressed between the three subpopulations which could be matched to enriched gene sets. We also investigated the transition process from cancer stem cell-like cells into more differentiated cell states. In the cancer stem cell population we found 14 significantly upregulated genes. Some of these potential breast cancer stem cell markers are associated to reported stem cell properties and clinical survival data, but further experimental validation is needed to confirm their cellular functions. Detailed characterization of cancer stem cells improve our understanding of mechanisms for tumor progression and contribute to the identification of new treatment targets.